Detection of chromosomal and plasmid-mediated mechanisms of colistin resistance in Escherichia coli and Klebsiella pneumoniae from Indian food samples. (March 2019) - Ghafur, Abdul; Shankar, Chaitra; GnanaSoundari, Palani; Venkatesan, Manigandan; Mani, Deepa; Thirunarayanan, M.A.; Veeraraghavan, Balaji
Highlights: Raw food samples ( n = 110) from Chennai, India, tested for colistin-resistant (Col-R) bacteria. 51 (46.4%) of the tested food samples had Col-R bacteria. The mcr-1 gene was identified in Col-R Escherichia coli . Mutations and insertional inactivation of the mgrB gene identified in Klebsiella spp. Abstract: Objectives: Numerous previous publications on the detection of bacterial isolates harbouring the mcr-1 gene from animals and humans strongly suggest an underlying route of transmission of colistin resistance via the food chain. The aim of this study was to investigate the presence of colistin-resistant (Col-R) bacteria in Indian food samples and to identify the underlying mechanisms conferring colistin resistance. Methods: Raw food material, including poultry meat, mutton meat, fish, fruit and vegetables, collected from food outlets in Chennai, India, were processed to identify Col-R bacteria using eosin methylene blue agar supplemented with colistin. Colistin minimum inhibitory concentrations (MICs) were determined by the broth microdilution method. PCR for the mcr-1 and mcr-3 genes was performed on Col-R Escherichia coli and Klebsiella pneumoniae isolates. Mutations in the mgrB gene were analysed in K. pneumoniae isolates. One representative mcr-1 -positive E. coli was subjected to whole-genome sequencing. Results: Of 110 food samples tested, 51 (46.4%) were positive for non-intrinsic Col-R Gram-negative bacteria. Three E. coli isolates were found to harbour mcr-1, whereas none were positive for mcr-3. Ten K. pneumoniae isolates had alterations in mgrB, with mutations in four and insertional inactivation in six. Conclusion: The presence of Col-R bacteria and the mcr-1 gene in raw food samples further complicates the antimicrobial resistance scenario in India. To the best of our knowledge, this is the first report in the global literature on mgrB mutation and its insertional inactivation conferring Col-R in K. pneumoniae from food samples.